A Study Based on the Helpful tool in the Initial Assessment of Ovarian Masses: Risk of Malignancy Index - Nighat Afroz, Nida Basharat, Sanaullah Khan, Ansa Khan, Misbah Jan, Ghulam Muhammad, Hasnat Shabbir (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To evaluate the Risk of Malignancy Index (RMI)for primary evaluation of ovarian masses. Materials and Methods: This was a prospective observational study conducted for period of two years at DHQ hospital Jhang. Study consisted of 141 female patients admitted for surgical exploration of ovarian masses. Pre-operative ultrasound evaluation of ovarian mass, menopausal status and CA125 were carried out for the patients. Based upon these finding RMI was calculated for all the patients. Post-operative histopathology of resected ovarian mass was done in all the cases to confirm the diagnosis. Results: sensitivity and specificity of CA125 alone at cut off value of 35 was 67.64 %, 83.17% respectively. Using RMI at cut off value of 200 sensitivity and specificity was 76.47%, 85.98 % respectively. Receiver operating characteristic curve (ROC)revealed that RMI was a better discriminate than CA125, ultrasound and menopausal status alone. Practical implication: We can easily apply this tool for detection of ovarian masses. Conclusion: Risk of malignancy index (RMI) is useful tool in primary evaluation of ovarian masses. It can be used to differentiate between benign and malignant ovarian masses with high sensitivity and specificity. Keywords: Risk, Cancer, Malignancy, Benign